Mitigative role of cysteamine against unilateral renal reperfusion injury in Wistar rats - Alabi, Babatunde Adebola; Nku-Ekpang, Okot-Asi; Lawal, Sodiq Kolawole; Iwalewa, Ezekiel Olugbenga; Omobowale, Temidayo; Ajike, Richard; Lawal, Ridwan Abiodun (Frontiers in Pharmacology, 2024)
Background Ischemia-reperfusion injury (IRI) is unavoidable during kidney transplant and it is responsible for delayed or non-function after kidney transplantation. Cysteamine is the standard drug in the management of nephropathic cystinosis and its extra-renal complications. Thus, we designed this study to investigate its potential against renal reperfusion injury. Results Significant elevation of H2O2, MDA, and nitrite and reduced GPx, GSH, and protein thiol in the Ischemia-reperfusion injury rats was reversed by cysteamine (50 and 100 mg/kg). Serum MPO, TNF-α, IL-1β, creatinine, and AOPP were significantly elevated in IRI while rats treated with cysteamine revealed a significant decrease (p < 0.05) in the activities of these pro-inflammatory and renal injury markers. Conclusion Based on its activity against inflammation, apoptosis, and free radical-induced stress, cysteamine has great potential to be used as a kidney transplant pre-operative drug to prevent renal reperfusion injury.